SUCCESS FACTORS FOR UNIVERSITY INCUBATORS - A BENCHMARKING MODEL FOR BETTER PERFORMANCE - Zoltán András Dániel; Patrícia Fanni Porkoláb (Köz-gazdaság, 2021)
Changing economic circumstances and technological advances are having an impact on the economic and social role of universities. Nowadays, university students, teachers and researchers are coming up with more and more innovative ideas, but they are unable to put their results into practice because of their lack of entrepreneurial skills. University incubators are specialised business incubators that create a link between university, business, and government, generating a significant impact on the local economy. In our research, we have highlighted the aspects that may be most relevant to the operation of 48 incubators in the world and analysed their performance. The comparative analysis allowed the creation of a standard model and the presentation of its success factors. KEYWORDS: university incubators, triple helix, competitiveness